Ultrastructural analysis of oral exfoliated epithelial cells of tobacco smokers and betel nut chewers: A scanning electron microscopy study - Sameera Shamim Khan; Balasundari Shreedhar; Mala Kamboj (Wolters Kluwer Medknow Publications, 2016)
Background: The study was undertaken to correlate epithelial surface pattern changes of oral exfoliated cells of tobacco smokers and betel nut chewers and also to compare them with patients of oral squamous cell carcinoma (OSCC) and healthy individuals. Materials and Methods: In this cross-sectional study, a total of fifty persons were included in the study, out of which thirty formed the study group (15 each tobacco smokers and betel nut chewers) and twenty formed the control group (ten each of OSCC patients - positive control and ten normal buccal mucosa - negative control). Their oral exfoliated cells were scraped, fixed, and studied under scanning electron microscope (SEM). The statistical analysis was determined using ANOVA, Tukey honestly significant difference, Chi-square test, and statistical SPASS software,P< 0.05. Results: OSCC, Individual cell modifications, intercellular relationships and surface characteristics observed by scanning electron microscopy between OSCC, tobacco smokers, betel nut chewers compared to normal oral mucosa have been tabulated. Conclusion: In normal oral mucosa, cell surface morphology depends on the state of keratinization of the tissue. Thus, it could prove helpful in detecting any carcinomatous change at its incipient stage and also give an insight into the ultra-structural details of cellular differentiations in epithelial tissues.